Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes

Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes

Isoprenoid emission of oak species typical for the Mediterranean area: Source strength and controlling variables - Steinbrecher, Rainer; Hauff, Karin; Rabong, Richard; Steinbrecher, Jutta (Atmospheric Environment, 1997)
easurements of isoprenoid emission on five Mediterranean oak species in the field revealed that Quercu.s frainetto, Quercus petraea and Quercus pubescens are strong emitters of isoprene. In contrast Quercus cerris and Quercus suber emitted no significant amounts of isoprene and monoterpenes. For Q. pubenscens and Q. frainetto median emission factors of 16.68 nmoIm-2s-1 (86.06 pgg-’ dw h-‘) and 30.72 nmolrn-2s-1 (133.95 pgg-’ dw h-l) were calculated, respectively. The 25 to 75 percentiles span of the emission factor data sets ranged from - 53% to + 56% of the median values. Light and temperature are the main controlling factors for isoprene emission. The influence of other environmental and plant physiological parameters on the isoprene emission is discussed. The “Guenther” emission algorithm is able to predict the daily maximum of the isoprene emission within the plant specific uncertainty range. However, the morning increase and the afternoon drop in the isoprene emission is not well parameterized. On the basis of process oriented models for the synthesis of isoprene in plants, a further reduction in the uncertainty may be achieved resulting in a more reliable prediction of short-time variation in isoprene emission
Keywords: biogenic voc; Emission factors; isoprene; Monoterpene; Quercus

Isoprenoid emission of oak species typical for the Mediterranean area: Source strength and controlling variables - Steinbrecher, Rainer; Hauff, Karin; Rabong, Richard; Steinbrecher, Jutta (Atmospheric Environment, 1997)
easurements of isoprenoid emission on five Mediterranean oak species in the field revealed that Quercu.s frainetto, Quercus petraea and Quercus pubescens are strong emitters of isoprene. In contrast Quercus cerris and Quercus suber emitted no significant amounts of isoprene and monoterpenes. For Q. pubenscens and Q. frainetto median emission factors of 16.68 nmoIm-2s-1 (86.06 pgg-’ dw h-‘) and 30.72 nmolrn-2s-1 (133.95 pgg-’ dw h-l) were calculated, respectively. The 25 to 75 percentiles span of the emission factor data sets ranged from - 53% to + 56% of the median values. Light and temperature are the main controlling factors for isoprene emission. The influence of other environmental and plant physiological parameters on the isoprene emission is discussed. The “Guenther” emission algorithm is able to predict the daily maximum of the isoprene emission within the plant specific uncertainty range. However, the morning increase and the afternoon drop in the isoprene emission is not well parameterized. On the basis of process oriented models for the synthesis of isoprene in plants, a further reduction in the uncertainty may be achieved resulting in a more reliable prediction of short-time variation in isoprene emission
Keywords: biogenic voc; Emission factors; isoprene; Monoterpene; Quercus